Blockchain Security as “People Security”: Applying Sociotechnical Security to Blockchain Technology - Nabben, Kelsie (Frontiers in Computer Science, 2021)
The notion that blockchains offer decentralised, ‘trustless’ guarantees of security through technology is a fundamental misconception held by many advocates. This misconception hampers participants from understanding the security differences between public and private blockchains - and adopting blockchain technology in suitable contexts. This paper introduces the notion of ‘people security’ to argue that blockchains hold inherent limitations in offering accurate security guarantees to people as participants in blockchain-based infrastructure, and the nature of the threats to participants, and the technical limitations differs between different types of blockchain architecture. It applies an existing socio-technical security framework to assess the social, software, and infrastructural layers of blockchain applications to reconceptualise ‘blockchain security’ as ‘people security’. A socio-technical security analysis of macro-social level blockchain systems surfaces social, technical and infrastructure layers and discrepancies between the technical and governance decisions that characterise the system, and the threats to participants using the network. The result of this is to identify a number of security and trust issues that need to be addressed, and categorise these against various blockchain architectures, participants and applications. Findings indicate that private blockchains have serious limitations for securing the interests of users in macro-social contexts, due to their centralised nature. In contrast, public blockchains reveal trust and security shortcomings at the micro and meso-organisational levels, yet, there is a lack of suitable desktop case studies by which to analyse socio-technical security at the macro-social level.